Severe, but not mild heat-shock treatment induces immunogenic cell death in cancer cells. (4th May 2017) - Adkins, Irena; Sadilkova, Lenka; Hradilova, Nada; Tomala, Jakub; Kovar, Marek; Spisek, Radek
ABSTRACT: The mechanisms of immunogenicity underlying mild heat-shock (mHS) treatment < 42°C of tumor cells are largely attributed to the action of heat-shock proteins; however, little is known about the immunogenicity of tumor cells undergoing severe cytotoxic heat-shock treatment (sHS > 43°C). Here, we found that sHS, but not mHS (42°C), induces immunogenic cell death in human cancer cell lines as defined by the induction of ER stress response and ROS generation, cell surface exposure of calreticulin, HSP70 and HSP90, decrease of cell surface CD47, release of ATP and HMGB1. Only sHS-treated tumor cells were efficiently killed and phagocytosed by dendritic cells (DCs), which was partially dependent on cell surface calreticulin. DCs loaded with mHS or sHS-treated tumor cells displayed similar level of maturation and stimulated IFNγ-producing CD8 + T cells without any additional adjuvants in vitro . However, only DCs loaded with sHS-treated tumor cells stimulated antigen-specific CD4 + T cells and induced higher CD8 + T-cell activation and proliferation. sHS-treated murine cells also exposed calreticulin, HSP70 and HSP90 and activated higher DC maturation than mHS treated cells. Vaccination with sHS-treated tumor cells elicited protective immunity in mice. In this study, we defined specific conditions for the sHS treatment of human lung and ovarian tumor cells to arrive at optimal ratio between effective cell death, immunogenicity and content of tumor antigens for immunotherapeutic vaccine generation.